Grasp interaction with tablets - Wolf, Katrin (T-Labs Series in Telecommunication Services,, 2015)
This book presents guidelines for a future device type: a tablet that allows ergonomic front- and back-of-device interaction. These guidelines help designers and developers of user interfaces to build ergonomic applications for tablet devices, in particular for devices that enable back-of-device interaction. In addition, manufacturers of tablet devices obtain arguments that back-of-device interaction is a promising extension of the interaction design space and results in increased input capabilities, enriched design possibilities, and proven usability. The guidelines are derived from empirical studies and developed to fit the users' skills to the way the novel device type is held. Three particular research areas that are relevant to develop design guidelines for tablet interaction are investigated: ergonomic gestures, interaction areas, and pointing techniques.